Falhas durante espatulação de cimentos endodônticos: Um estudo de biocompatibilidade in vivo - Bueno, Carlos Roberto Emerenciano [UNESP]; Lopes, Gustavo Arcos [UNESP]; Valentim, Diego; Marques, Vanessa Abreu Sanches [UNESP]; Vasques, Ana Maria Veiga [UNESP]; Cury, Marina Tolomei Sandoval [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Jacinto, Rogério de Castilho [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Dezan Junior, Eloi [UNESP] (Editora Cubo, 2017)
Objectives: Evaluate, in vivo, the influence of mixing failures on endodontic sealers. Material and Methods: To alveolus analysis, 80 rats were divided into Sealapex® and AH Plus® groups. Within each group, the sealer was subjected to either partial (incomplete homogenization— simulating handling failures) or total mixing (complete homogenization) over two periods of 7 and 30 days (n = 20). The maxillary incisor was extracted and a polyethylene tube containing the sealer was inserted. To quantify edema, 40 male rats were divided into four groups (n = 10). The animals received 2% Evans Blue intravenously, and either AH Plus® or Sealapex® was injected subcutaneously. The rats were euthanized after 3 or 6 hours and analyzed in a spectrophotometer (630 ƞm). To analyze the subcutaneous tissue, 20 rats received polyethylene tube implants with the sealers in the dorsal area (n=10), then euthanized after either 7 or 30 days, and inflammation was evaluated according to an inflammatory cells score. Results: In the alveolar 7-day group, control group presented an inflammation score 1, while all other groups presented a score 2, except AH plus® total mix group (3). After 30 days, all groups presented a score 1. The edemogenic test showed less edema in Sealapex® groups (p < 0.5). In subcutaneous 7-day period, all groups presented score 2. In 30 days, all groups revealed score 1, except AH Plus® partial mix group (2). Conclusion: Regarding mixing of the sealers, there were no significant differences among the groups.
Mixing failures of endodontic sealers: An in vivo biocompatibility study
Keywords: AH Plus; Inflammation; Materials testing; Root canal filling materials; Sealapex